2017
DOI: 10.1111/ijcs.12344
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of consumer price consciousness in a turbulent economy

Abstract: Major economic crises create financial and normative stressors, affecting consumers long after economies technically leave recession. Consumer adaptations to these stressors challenge researchers’ and marketers’ assumptions of well‐established concepts and theories, notably consumer price consciousness (CPC). We examine this pivotal marketing construct within the domains of stress and coping during times of economic turbulence. In this paper, the authors develop and test a conceptual model, then present implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 88 publications
4
50
0
1
Order By: Relevance
“…Different aspects of crises and consumption are being examined including the changing process of household budget allocations (Du & Kamakura, 2008;Kamakura & Du, 2012), consumer price consciousness (Hampson & McGoldrick, 2017), calculative price behavior (Berdysheva & Romanova, 2017), the role of private labels and discount stores (Puelles et al, 2016;Lamey, Deleersnyder, Dekimpe, & Steenkamp, 2007), adaptive shopping patterns (Hampson & McGoldrick, 2013), consumers' money attitudes in the postrecession economy (Hampson et al, 2018), social and political discourses (Alonso, Rodríguez, & Rojo, 2015, media discourses (Vihalemm, Keller, & Pihu, 2016), ethnocentric consumption (Lekakis, 2017), social innovation and community-based responses (Blättel-Mink et al, 2017), communal exchange and social resilience (Garner, 2017) and collaborative consumption (Lindlbom & Lindlbom, 2017).…”
Section: Crises Business Dynamics and Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different aspects of crises and consumption are being examined including the changing process of household budget allocations (Du & Kamakura, 2008;Kamakura & Du, 2012), consumer price consciousness (Hampson & McGoldrick, 2017), calculative price behavior (Berdysheva & Romanova, 2017), the role of private labels and discount stores (Puelles et al, 2016;Lamey, Deleersnyder, Dekimpe, & Steenkamp, 2007), adaptive shopping patterns (Hampson & McGoldrick, 2013), consumers' money attitudes in the postrecession economy (Hampson et al, 2018), social and political discourses (Alonso, Rodríguez, & Rojo, 2015, media discourses (Vihalemm, Keller, & Pihu, 2016), ethnocentric consumption (Lekakis, 2017), social innovation and community-based responses (Blättel-Mink et al, 2017), communal exchange and social resilience (Garner, 2017) and collaborative consumption (Lindlbom & Lindlbom, 2017).…”
Section: Crises Business Dynamics and Consumptionmentioning
confidence: 99%
“…There is an empirical demonstration that during recessions consumers become more concerned about their financial security (e.g., Kamakura & Du, 2012;Xiao and O'Neill, 2016;Zurawicki & Braidot, 2005), more frugal and more price conscious (Hampson & McGoldrick, 2017;Hampson & McGoldrick, 2013;Steenkamp & Maydeu-Olivares, 2015).…”
Section: Consumers' Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their paper shows nicely how crises induce changes in the appreciation of prices and how this in turn aggregates to a new norm of consumer behaviour. Hampson and McGoldrick () explore the impact of financial well‐being and frugality norms on consumer price consciousness, showing that economic resources are a prime explanation of price consciousness (forming an important component of the appreciation dimension of consumption). The contributions to this issue refer to the long‐term impact of crisis: in parallel with the immediate and tangible responses that affect the supply and require adaptations from producers and marketers (see Hampson & McGoldrick in this issue) the more intangible co‐effects of the consumers’ resilience can also lead to the gradual transformation of values, identities and initiate new forms of exchange (see Figure ).…”
Section: Contributions Of the Papers Of The Special Issuementioning
confidence: 99%
“…Prior research has shown that price conscious behavior is an adaptive response for people experiencing money-related negative affect. For example, in the context of the Great Recession of the late 2000s, price consciousness emerged as a principle coping strategy through which UK consumers sought to mitigate heightened feelings of financial fear and guilt ( Hampson & McGoldrick, 2017 ). Perceived financial vulnerability associates with a range of sub-optimal outcomes, including material deprivation, reduced vitality of social relationships, and physical and mental health problems ( O’Loughlin et al, 2017 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%